Theoretical method for the estimation of vapour conductivity for unsaturated soil - Zhai, Qian (2022)
The liquid water movement is commonly considered in the seepage analysis related to the unsaturated soil (e.g, residual soil above the ground water table). The hydraulic conductivity of unsaturated soil is commonly considered to decrease with the increase in soil suction (or decrease in the degree of saturation). As a result, the estimated hydraulic conductivity of unsaturated soil from the conventional method is very low in the high suction range (i.e., beyond the residual suction). However, the experimental results from recent studies indicate that in the high suction zone, the hydraulic conductivity of unsaturated soil may increase with an increase in soil suction. In addition, recent studies also indicate that in the high suction zone (i.e., greater than 3100 kPa), water in soil moves mainly in the vapour form. As a result, the estimation of the hydraulic conductivity of unsaturated soil due to vapour flow in soil is crucial for engineers in the estimation of water transmission through a relative dry soil. In this note, the theoretical method is proposed for the estimation of vapour conductivity from the soil-water characteristic curve. The proposed method is rational and it has the theoretical basis without any empirical parameter. It is observed that the estimated results from the proposed method agree well with the results reported in the published literature.